Estonian Caddisflies (Insecta: Trichoptera). An annotated checklist - Viidalepp, Jaan; Timm, Henn; Salokannel, Juha (Entomologica Fennica, 2011)
Achecklist of 190 species of Estonian caddisflies is compiled based on literature and voucher material in collections at Estonian University of Life Sciences. 31 species are listed first time for the country while 159 taxa were referred to in literature. Two taxa are rejected as possible misidentifications (Diplectrona felix and Molanna submarginalis). 25 species are listed in Estonian Red Data book. Geographical distribution of Trichoptera both in Estonia and along the east shore of Baltic Sea is reviewed in brief.